Consumer Search and Oligopolistic Pricing: An Empirical Investigation - Maarten C.W. Janssen; Jose Luis Moraga-Gonzalez; Matthijs R. Wildenbeest (Tinbergen Institute, 2004)
This paper presents an empirical examination of oligopoly pricingand consumer search. The theoretical model allows for sequential andnon-sequential search and using the theoretical restrictions firm andconsumer behavior impose on the data we study the empirical validity of themodels. Two equilibria arise: one with costless search and the other withcostly search. We find that the costless search equilibrium works well forproducts with a relatively low value, and, by implication, a small number ofsellers. By contrast, the costly search equilibrium explains the observeddata in a manner that is consistent with the underlying theoretical modelfor almost all products (for 86 out of 87!).
Keywords: C13; D40; L13; 330; consumer search; oligopoly; price dispersion; maximum likelihood estimation; Konsumentenverhalten; Informationskosten; Suchtheorie; Oligopol; Theorie